E-government and social media: the Queensland Government's MYQ2 initiative - Allen, Matthew; Balnaves, Mark (Austrian Computer Society (Osterreichishe Computer Gesellschaft), 2010)
In 2008 the government of Queensland, Australia launched a strategic vision for the state and its people entitled Toward Q2. Like many government media activities, the vision was articulated primarily via the Internet: a commonplace form of e-government. Yet Toward Q2 is soon to be accompanied by a more innovative form of e-government through another initiative - MyQ2. MyQ2 is a website that aims to harness the power of social media in building governmental interaction with citizens. This paper will focus on describing MyQ2 in its pre-release form, so as to demonstrate how it represents a new form of e-government, building civic engagement, while doing so in a way specific to the needs of government. MyQ2 demonstrates how the use of Web 2.0-based approaches enables governments, in theory at least, to mobilise citizens to become active participants in the operational achievement of governance.